Pemanfaatan Aplikasi Google dalam Pembelajaran IPS untuk Meningkatkan Kemampuan Kognitif Siswa di SMP Swasta Kita Membangun Bukit Harapan II - Sinaga, Natalia (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the impact of using Google applications on students' cognitive abilities in Social Studies (IPS) learning at SMP Swasta Kita Membangun Bukit Harapan II. A qualitative descriptive method was employed, utilizing observation, interviews, and documentation as data collection techniques. The findings indicate that Google applications, such as Google Classroom, Google Meet, and Google Forms, effectively enhance students' abilities through quick access to information, interactivity, and collaborative learning. Success factors include technological support, teacher skills, and student interest, while challenges involve limited infrastructure, lack of teacher training, and varying student motivation. Solutions include teacher training, infrastructure improvement, and diverse learning strategies.